2014
DOI: 10.1038/npp.2014.295
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Cholinergic System in Hyperactivity in Dopamine-Deficient Mice

Abstract: Dopaminergic systems have been known to be involved in the regulation of locomotor activity and development of psychosis. However, the observations that some Parkinson's disease patients can move effectively under appropriate conditions despite low dopamine levels (eg, kinesia paradoxia) and that several psychotic symptoms are typical antipsychotic resistant and atypical antipsychotic sensitive indicate that other systems beyond the dopaminergic system may also affect locomotor activity and psychosis. The pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 34 publications
(38 reference statements)
1
30
0
Order By: Relevance
“…L-DOPA administration also had effects on other grooming parameters. The main effect was a general increase in total grooming duration, an effect that could be related to the increase of general activity stimulated by L-DOPA [ 28 ]. In addition, we did not observe any L-DOPA effect on the frequency of complete grooming, suggesting a lack of efficiency of L-DOPA to restore sequence completion that was altered by the 6-OHDA lesion.…”
Section: Discussionmentioning
confidence: 99%
“…L-DOPA administration also had effects on other grooming parameters. The main effect was a general increase in total grooming duration, an effect that could be related to the increase of general activity stimulated by L-DOPA [ 28 ]. In addition, we did not observe any L-DOPA effect on the frequency of complete grooming, suggesting a lack of efficiency of L-DOPA to restore sequence completion that was altered by the 6-OHDA lesion.…”
Section: Discussionmentioning
confidence: 99%
“…We previously found that dopamine‐deficient mice became hypoactive 24 h after the last l ‐DOPA injection, when striatal dopamine levels were low but could be detected. Unexpectedly, dopamine‐deficient mice became hyperactive in a novel environment 72 h after the last l ‐DOPA injection (Fig. ).…”
Section: Strategy To Investigate Dopamine‐independent Opioid Rewardmentioning
confidence: 94%
“…Nest building (Data S3) was assessed by leaving a mouse in a cage that was covered with a Palsoft Sheet Type (ie, a sheet‐type bedding material; Oriental Yeast, Tokyo, Japan) for one night, followed by visual examination of the formation of a nest. Locomotor activity (Data S1) was assessed in a novel environment as described previously using a Supermex apparatus (Muromachi Kikai, Tokyo, Japan) and a sensor monitor that was mounted above the chamber. Each mouse was exposed to an illuminated chamber (30 cm × 40 cm × 25 cm).…”
Section: Main Textmentioning
confidence: 99%